2015
DOI: 10.1097/icb.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of Sickle Cell Maculopathy

Abstract: This report provides evidence that optical coherence tomography angiography may be more sensitive in detecting macular capillary nonperfusion than fluorescein angiography. It also provides further evidence that the ischemic vasculopathy of sickle cell retinopathy preferentially affects the deep capillary plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…[44-51] Some of these silent findings have been shown to be significantly associated with the presence of PSR. [49]…”
Section: Resultsmentioning
confidence: 99%
“…[44-51] Some of these silent findings have been shown to be significantly associated with the presence of PSR. [49]…”
Section: Resultsmentioning
confidence: 99%
“…The nonperfusion of capillaries in the deep layer seen on OCTA has been reported in various retinal diseases. 6,20,[39][40][41][42] When compared with the superficial plexus, the deep capillaries may be more prone to ischemia because they are positioned in a watershed-like region and are not directly connected to arterioles. 43,44 The major blood vessels are found in the thickest portions of the RNFL, which are located in the superior and inferior regions.…”
Section: Discussionmentioning
confidence: 99%
“…1317 Recent reports have shown that UWFA, which captures up to twice as much retinal area as conventional fluorescein angiography (FA) 18 , is more sensitive than traditional FA in identifying peripheral vascular changes in sickle retinopathy. 14 Additionally, proliferative sickle retinopathy has been found to be more prevalent in patients with macular thinning identified on SD-OCT suggesting the utility of SD-OCT in identifying patients at higher risk for proliferative disease.…”
Section: Introductionmentioning
confidence: 99%